Critics of Democratic Peace Theory: From Realism to Constructivism - E. S. Okuneva (Сравнительная политика, 2015)
This article is devoted to the critique of the ‘democratic peace’ theory by various schools of IR theory, including Realism, Liberalism and Constructivism.